2022
DOI: 10.1111/jfpp.16591
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the microwave parameters correlating effects on total recovery of bioactive alkaloids from sesame leaves using orthogonal matrix and artificial neural network integration

Abstract: In this study, the microwave‐assisted processing of Sesamum indicum leaves was intensified to predict the total alkaloid content via Taguchi orthogonal design and neural network model. Under the optimum microwave condition, the maximized alkaloid content was estimated to be 15.40 (mg/g) % using irradiation time (A) of 60 sec, microwave power (B) of 300 W, oven temperature (C) of 60°C, the mass ratio (D) of 12.5 g/ml, and solvent concentration (E) of 80%. The significant effects of each microwave extraction par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Furthermore, when the number of iterations in the training process was increased, the mean square error produced from the training process showed a minor decrease in magnitude. The lower RMSE values further supported the validity of a solid training programme and improved prediction [ 17 ]. As indicated in the graph, the best fit point occurs at epoch number five.…”
Section: Training and Neural Network Analysismentioning
confidence: 53%
See 1 more Smart Citation
“…Furthermore, when the number of iterations in the training process was increased, the mean square error produced from the training process showed a minor decrease in magnitude. The lower RMSE values further supported the validity of a solid training programme and improved prediction [ 17 ]. As indicated in the graph, the best fit point occurs at epoch number five.…”
Section: Training and Neural Network Analysismentioning
confidence: 53%
“…Artificial neural network (ANN) is an intelligent modelling tool that deals with non-linear behaviour of inputs and desired outputs data [ 16 ]. The relationship between several input and output variables can be easily reached by optimization [ 17 ]. It has been reported that Grey-Taguchi combined with ANN enhances process performance [ 11 ].…”
Section: Introductionmentioning
confidence: 99%